2021
DOI: 10.3329/ajmbr.v7i2.54997
|View full text |Cite
|
Sign up to set email alerts
|

Fish culture in net cages improves the livelihood of Charland population: a case study from Padma (Ganga) River, Munshiganj, Bangladesh

Abstract: Char dwellers are considered poorer than the mainland population. A constant threat of riverbank failure, flooding, and seasonal cyclone, combined with lack of physical infrastructures, and employment opportunities in the Chars, makes a vulnerable, difficult, and fragile life. The aim of the present work was an initiative to improve the livelihood of Char dwellers through fish culture in the net cages. A focus group survey was conducted on Char dwellers to know about the livelihood conditions. Quantitative and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…In this study, a number of 23 various species of phytoplankton were classified into four different groups from the study area. The majority of these phytoplanktons were consistently highlighted by Uddin et al (2022) [ 18 ]; and [ 19 ]. Uddin et al [ 20 ] found 29 species of phytoplankton belonging to 8 major classes from the rivers of Sundarbans.…”
Section: Discussionmentioning
confidence: 69%
“…In this study, a number of 23 various species of phytoplankton were classified into four different groups from the study area. The majority of these phytoplanktons were consistently highlighted by Uddin et al (2022) [ 18 ]; and [ 19 ]. Uddin et al [ 20 ] found 29 species of phytoplankton belonging to 8 major classes from the rivers of Sundarbans.…”
Section: Discussionmentioning
confidence: 69%
“…Some fishers communities were also observed health effects, such as skin rashes, burns, and waterborne diseases, especially after extreme events such as floods and hurricanes found by Furgal and Seguin, (2006). Even if not numerous, these observations supported the research of Patz et al, (2005); Islam et al, (2020a);and Saha et al, (2021), which suggested an increase in some diseases due to climate change. Because of the reduction in fish production, fishers did not earn enough money to maintain their family appropriately.…”
Section: Impacts Of Weather and Climatic Variable Perception Of Coast...mentioning
confidence: 68%